Iterative methods for solving split feasibility problem in Hilbert space - Kilicman, Adem; Mohammed, Lawan Bulama (Institute for Mathematical Research, Universiti Putra Malaysia, 2016)
Based on the recent work of Wang et al. (2012), in this paper, we construct a new algorithm for solving split feasibility problem for the class of total quasi-asymptotically nonexpansive and uniformly τ−Lipschitzian mappings in Hilbert space and prove its strong convergence result. The result presented in this paper, not only extend the result of Wang et al. Wang et al. (2012), but also extend, improve and generalize several well-known results in the literature.